2015
DOI: 10.4081/vsd.2015.5892
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and glucose responses in juvenile striped catfish subjected to a cold shock

Abstract: Cold-shock stress happens when a fish had been adjusted to a specific water temperature or range of temperatures and is consequently exposed to a rapid drop in temperature, resulting in a cascade of physiological and behavioral responses and, in some cases, death. In the current study, the stress response of striped Catfish (Pangasianodon hypophthalmus) was studied by evaluating serum cortisol and glucose level following an abrupt reduction in water temperature (from 28°C to 15°C) at different time points (pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Panase et al (2018) cold stressed Nile tilapia (25 to 13 C at 3 C per h, held at 13 C for up to 3 days) and observed initial decreases followed by gradual increases in serum glucose and nitrogenous waste in the blood over the sampling period, along with fluctuations in serum cholesterol and gradual increases in alanine and aspartic transaminases likely released into the bloodstream as a result of liver damage. Nonetheless, relative to ambient temperature controls, serum glucose levels did not change following 24 h cold shock (c. 27.5 to 15 C) in iridescent shark catfish, though both control and cold-shocked groups exhibited slight fluctuations over the 24 h period (Adloo et al, 2015). Blood glucose in bonefish was unaffected by 2 h exposure to a decrease in temperature by 7 or 14 C; nonetheless, blood lactate was elevated in the À14 C group relative to a handling control (Szekeres et al, 2014).…”
Section: Haematological Parametersmentioning
confidence: 68%
See 2 more Smart Citations
“…Panase et al (2018) cold stressed Nile tilapia (25 to 13 C at 3 C per h, held at 13 C for up to 3 days) and observed initial decreases followed by gradual increases in serum glucose and nitrogenous waste in the blood over the sampling period, along with fluctuations in serum cholesterol and gradual increases in alanine and aspartic transaminases likely released into the bloodstream as a result of liver damage. Nonetheless, relative to ambient temperature controls, serum glucose levels did not change following 24 h cold shock (c. 27.5 to 15 C) in iridescent shark catfish, though both control and cold-shocked groups exhibited slight fluctuations over the 24 h period (Adloo et al, 2015). Blood glucose in bonefish was unaffected by 2 h exposure to a decrease in temperature by 7 or 14 C; nonetheless, blood lactate was elevated in the À14 C group relative to a handling control (Szekeres et al, 2014).…”
Section: Haematological Parametersmentioning
confidence: 68%
“…Adloo et al . (2015) observed similar gradual increases in serum cortisol over 24 h in both an ambient control group and a cold shock ( c . 27.5 to 15°C for up to 24 h) group of iridescent shark catfish ( Pangasianodon hypophthalmus Sauvage 1878).…”
Section: Cold Stress and The Generalized Stress Response In Fishmentioning
confidence: 74%
See 1 more Smart Citation
“…There are abundant essays about the domestication effects on growth and stress response in teleosts [20,21]. It has been reported that domestication reduces fish stress response, manifesting less fear in salmonids and European sea bass or less sensitiveness to acute handling stressors in Eurasian perch and catfish [22,23]. The cold-tolerant fugu used in this experiment also obtained low-temperature domestication.…”
Section: Discussionmentioning
confidence: 86%